Generalized Buzano inequality - Bottazzi, Tamara Paula (2023)
If P is an orthogonal projection defined on an inner product space H, then the inequality (formula presented) fulfills for any (formula presented). In particular, when P is the identity operator, then it recovers the famous Buzano inequality. We obtain generalizations of such classical inequality, which hold for certain families of bounded linear operators defined on H. In addition, several new inequalities involving the norm and numerical radius of an operator are established.